Patient characteristics associated with screening positive for Alzheimer’s disease and related dementia - Fowler NR (Dove Medical Press, 2018)
Nicole R Fowler,1–4 Anthony J Perkins,4 Sujuan Gao,5 Greg A Sachs,1–3 Austin K Uebelhor,2,3 Malaz A Boustani1–4 1Department of Medicine, Indiana University School of Medicine, Indianapolis, IN, USA; 2Indiana University Center for Aging Research, Indianapolis, IN, USA; 3Regenstrief Institute, Inc., Indianapolis, IN, USA; 4Center for Health Innovation and Implementation Science, Indiana Clinical and Translational Science Institute, Indianapolis, IN, USA; 5Department of Biostatistics, Indiana University School of Medicine, Indianapolis, IN, USA Introduction: Screening all older adults for Alzheimer’s disease and related dementias (ADRD) in primary care may not be acceptable or feasible. The goal of this study was to identify factors that could optimize screening in primary care and enhance its feasibility.Methods: This is a cross-sectional study in rural, suburban, and urban primary care practices in Indiana. A total of 1,723 patients ≥65 years of age were screened for ADRD using the Memory Impairment Screen. Logistic regression was used to identify patient-specific factors associated with screening positive for ADRD.Results: The positive screening rate was 4.9%. Rates varied significantly across the three study sites. The rural site had the lowest rate (2.8%), which was significantly lower than the rates at the suburban (5.6%) and urban (6.6%) sites (P<0.01). Patient age, sex, and education were significantly (P<0.05) associated with screening positive for ADRD.Conclusion: Targeted screening of patients at risk for ADRD may represent a more optimal and feasible screening alternative to population screening. Keywords: dementia screening, Alzheimer’s disease screening, primary care